Preparation of Improved p-n Junction NiO/TiO2 Nanotubes for Solar-Energy-Driven Light Photocatalysis. (7th February 2013) - Sim, Lan Ching; Ng, Kai Wern; Ibrahim, Shaliza; Saravanan, Pichiah
Abstract : Self-organized TiO2 nanotubes (TNTs) with average inner diameter of 109 nm, wall thickness of 15 nm, and tube length of 7–10  μ m were loaded with nickel oxide (NiO) nanoparticles via incipient wet impregnation method. The molar concentration of Ni(NO3 )2 ·6H2 O aqueous solution varied in a range of 0.5 M–2.5 M. The samples were characterized for crystalline phase, morphology, topography, chemical composition, Raman shift, and UV-Vis diffusion reflection properties. The finding shows that the loading of NiO did not influence the morphology, structure, and crystalline phase of TNTs but it exhibited significant effect on crystallite size and optical absorption properties. Further, the solar-energy-driven the photocatalytic activity of NiO/TNTs and pure TNTs was evaluated by degrading methylene blue (MB). The results confirm that photocatalytic efficiency of NiO/TNTs is higher than that of TNTs.